Cobalt Boryl Complexes: Enabling and Exploiting Migratory Insertion in Base‐Metal‐Mediated Borylation1. (26th June 2015) - Frank, René; Howell, James; Campos, Jésus; Tirfoin, Rémi; Phillips, Nicholas; Zahn, Stefan; Mingos, D. Michael P.; Aldridge, Simon
Abstract Cobalt boryl complexes, which have only been sporadically reported, can be accessed systematically with remarkable (but controllable) variation in the nature of the MB bond. Complexes incorporating a very strong trans σ‐donor display unparalleled inertness, reflected in retention of the MB bond even in the presence of extremely strong acid. By contrast, the use of the strong π‐acceptor CO in the trans position, results in significant CoB elongation and to labilization of the boryl ligand via unprecedented CO migratory insertion. Such chemistry provides a pathway for the generation of coordinative unsaturation, thereby enabling ligand substitution and/or substrate assimilation. Alkene functionalization by boryl transfer, a well‐known reaction for noble metals such as Rh or Pt, can thus be effected by an 18‐electron base‐metal complex.